2017
DOI: 10.1002/anie.201710856
|View full text |Cite
|
Sign up to set email alerts
|

A Vinyl Sulfone‐Based Fluorogenic Probe Capable of Selective Labeling of PHGDH in Live Mammalian Cells

Abstract: Chemical probes are powerful tools for interrogating small molecule-target interactions. With additional fluorescence Turn-ON functionality, such probes might enable direct measurements of target engagement in live mammalian cells. DNS-pE (and its terminal alkyne-containing version DNS-pE2) is the first small molecule that can selectively label endogenous 3-phosphoglycerate dehydrogenase (PHGDH) from various mammalian cells. Endowed with an electrophilic vinyl sulfone moiety that possesses fluorescence-quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Consequently, probe 6 can be used for both in situ profiling and two-photon fluorogenic imaging of cellular enzyme activities. These successful examples, which are combined with no-washing drug imaging and chemoproteomics, have inspired researchers to develop multi-functional conjugates capable of providing more insightful information in drug discovery [ [36] , [37] , [38] ].…”
Section: Non-cleavable Conjugatesmentioning
confidence: 99%
“…Consequently, probe 6 can be used for both in situ profiling and two-photon fluorogenic imaging of cellular enzyme activities. These successful examples, which are combined with no-washing drug imaging and chemoproteomics, have inspired researchers to develop multi-functional conjugates capable of providing more insightful information in drug discovery [ [36] , [37] , [38] ].…”
Section: Non-cleavable Conjugatesmentioning
confidence: 99%
“…For example, Yaoa nd co-workersr eported the SCF13 linker consisting of aq uenching vinyl sulfone and an onquenching propargyl moiety. [65] SCF13 selectively labels 3-phosphoglycerate dehydrogenase (PHGDH) [67] through the reactiono ft he vinyl sulfone and thiol moietiesi nP HGDH, leading to emission turn-on and imaging of endogenous PHGDH activity.I na ddition, the propargyl moiety of SCF13 was subsequently linked to commerciallya vailable azide-biotin (N 3 -biotin)t hrough the CuAAC reactionf or enrichmenta nd purification by streptavidin-coated beads (Figure 14 a). Zhou et al reported the azido-and hydrazine-functionalized SCF14 linker, [66] the emission of which was initially quenched by the hydrazine moiety through the PET mechanism [68] for the fluorogenic labelingo f5fC [69] by ah ydrazine-aldehyde reaction that enabled fluorescent visualization of PAGE bands.…”
Section: Hetero-bifunctional Scf Linkersmentioning
confidence: 99%
“…In contrast to SCF linkers,D CF linkerso nly exhibit emission turn-onu pond ual reaction-enabled conjugate formation, allowingt he one-pot fabrication of bioconjugates and fluorescent assay.H owever,t he design and synthesis of profluoro- Figure 14. Hetero-bifunctional SCF linkers for both labeling and functionality.a)SCF13a nd b) SCF14s electively and fluorogenically label PHGDH [65] and 5-formylcytosine (5fC) [66] for in vivo imagingand PAGE visualization, respectively, followed by biotin functionalizationfor furtherenrichment and quantification. Figure 15.…”
Section: Homo-bifunctional Dcf Linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…[6d], On the other hand, the terminal vinyl sulfonyl compounds have been recognized as a significant covalent‐bonds‐formation tool in bioconjugation of proteins, polymers, carbohydrates type of biomolecules, fluorescent,[11a], electrochemically active[11a], or affinity‐binding tags. [11a], In addition, the terminal vinyl sulfone‐based fluorogenic probes (Figure , I and II ) have recently been developed as potential covalent pharmacophores for selectively labeling in living cells. Additionally, terminal olefins are prevalent in natural products, (Figure ) such as acremonide ( III ), and ruguloxanthones C ( IV ) .…”
Section: Introductionmentioning
confidence: 99%